Edukasi dan Pendampingan Sertifikasi Produk Halal dalam Mendorong UMKM Berdaya Saing Global - Qoidul Khoir; Siti Maimunah; Holilah Holilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
The global halal market, projected to reach USD 3.2 trillion by 2028, presents significant opportunities for micro, small, and medium enterprises (MSMEs) in Indonesia, including East Java, which has a strong food and beverage MSME base. However, the low literacy level of MSME actors regarding halal certification regulations and procedures is a constraint in increasing competitiveness in the global market. This Community Service (PKM) activity aims to provide comprehensive education and guidance on halal product certification for mentored MSMEs in several districts/cities in East Java, so that they are able to obtain halal certification and expand market access. This community service method uses the ABCD (Asset Based Community Development) approach, which begins with discovering the potential of MSMEs, dreaming of a vision for halal competitiveness, designing training and mentoring programs, and delivering real actions in the certification process. The activities were carried out thru focus group discussions, socialization and technical training, assistance in filling out halal certification documents on the BPJPH system, and field verification assistance. The service results showed a significant increase in participants' understanding of halal certification procedures from 56% to 92% (based on pre-test and post-test results), as well as the success of 70% of the participating MSMEs in obtaining a Halal Certificate (SH) from BPJPH. This activity not only accelerated the halal certification process but also increased consumer confidence and expanded marketing networks. This PKM recommends program sustainability thru the establishment of university-based Halal Centers to continuously support MSMEs. Keywords: Education, and Mentoring, Halal Certification, MSMEs